RANCANG BANGUN APLIKASI WEBSITE YAYASAN BINA INSAN CENDIKIA LUKMANUL HAKIM KABUPATEN GOWA - W. Hasyim , Muhammad Miftahurrahman; astian, Alvian B; Muh. Ahyar (Journal of Informatics and Computer Engineering Research, 2025)
This study aims to design and develop an official website for the Bina Insan Cendikia Lukmanul Hakim Foundation by utilizing Visual Studio Code technology and the PhpMyAdmin database. The formulation of the problem raised in this study includes how to design an effective website in presenting foundation information and providing convenience for the public to participate through online donations. The benefits of developing this website include increasing the transparency of the foundation, facilitating public access to information, and encouraging active participation in foundation programs. As a solution, this study presents essential features such as foundation profiles, donation pages, and registration, all of which are designed to meet the information and interaction needs of users. The evaluation results show that this website has succeeded in achieving its stated goals, supporting the dissemination of foundation information, and facilitating participation effectively, with an average eligibility score of 92.6%, indicating that this website has succeeded in achieving its stated goals. Users highly rate the aspects of ease of use, attractive appearance, and completeness of the information presented.